Critical Discourse Analysis on Nadia Omara Podcast - Muftiah; Ulinsa; Arum Pujining Tyas; Yunidar; Juliah Marfuah (Universitas Islam Negeri Palopo, 2026)
This study aims to analyze the structure of discourse on Nadia Omara's podcast using the Critical Discourse Analysis (AWK) model of Teun A. Van Dijk. The focus of this research is to examine the macrostructure, superstructure, and microstructure in the podcast narrative, especially in the episode